Development and implementation of autism standards for prisons. (9th June 2015) - Lewis, Alexandra; Pritchett, Robert; Hughes, Clare; Turner, Kim
Abstract : Purpose: – The purpose of this paper is to describe the experience of a southern English young offenders institution in developing and implementing standards to improve awareness and care of prisoners with autistic spectrum disorders (ASD). Design/methodology/approach: – Some contextual factors driving the project are discussed, the multi-agency process involved in the development and implementation of the standards is described and recommendations are made regarding implementation of the standards in other settings. Findings: – It is expected that successful implementation of the standards will reduce the level of distress and difficulty experienced by people with ASD who find themselves in custody, it will also improve the prison's ability to meet the needs of prisoners with ASD and thereby improve rehabilitation and reduce any adverse impact on everyday operational processes. Demonstrating success in meeting the standards will enable the prison to achieve accreditation by the National Autistic Society. In March 2015 the prisons minister encouraged all prisons to follow this approach and this will have practice and resource implications. Originality/value: – This paper describes a clear framework which prisons can use to work systematically towards achieving good practice in addressing the needs of prisoners with ASD. It will enable prisons to meet the duties imposed on them by the Autism Act, 2009 and the Equalities Act, 2010.